The politics of monitoring and evaluation: Implications for evidence generation and use - Ismael Ochen-Ochen (African Evaluation Journal)
Background: Monitoring and evaluation (ME) is not only a managerial tool and apolitical process, but it is also a political tool serving political objectives. In Western Uganda, government and non-governmental conservation organisations monitor and evaluate Community-Based Natural Resources Management (CBNRM) projects in protected areas (PAs) and adjacent communities. However, politics of ME influences how performance evidence is generated and used.